Myth, Symbol, and Colonial Encounter : British and Mi'kmaq in Acadia, 1700-1867 - Jennifer Reid (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 1995)
From the time of the Treaty of Utrecht in 1713, people of British origin have shared the area of New Brunswick, Nova Scotia, and Prince Edward Island, traditionally called Acadia, with Eastern Canada's Algonkian-speaking peoples, the Mi'kmaq. This historical analysis of colonial Acadia from the perspective of symbolic and mythic existence will be useful to those interested in Canadian history, native Canadian history, religion in Canada, and history of religion.